Achievement of Low-Density Lipoprotein Cholesterol Targets in CKD - Ziad A. Massy (Kidney International Reports, 2019)
Introduction: We describe the characteristics of patients with moderate/advanced chronic kidney disease (CKD) according to receipt of lipid-lowering therapy (LLT), and whether they achieved low-density lipoprotein cholesterol (LDL-C) targets for high- and very high-risk patients. Methods: CKD-REIN (NCT03381950), a prospective cohort study conducted in 40 nephrology clinics in France, enrolled 3033 patients with moderate (stage G3) or advanced (stage G4/G5) CKD (2013−2016) who had not been on chronic dialysis or undergone kidney transplantation. Data were collected from patients’ interviews and medical records. Patients were followed up at 1 year. Results: Among 2542 patients (mean [SD] age 67 [13] years, 34% women) with LDL-C measurements at baseline (mean [SD] LDL-C 2.7 [1.1] mmol/l; cholesterol 4.8 [1.3] mmol/l), 63% were on LLT; 24% were at high (CKD stage G3, no cardiovascular disease [CVD] or diabetes) and 74% at very high (CKD stage G3 with diabetes or CVD, or CKD stage G4/5) cardiovascular risk. Among high-risk patients, 45% of those on statin and/or ezetimibe achieved the LDL-C treatment target (<2.6 mmol/l). Among very high-risk patients, the percentage at goal (<1.8 mmol/l) was 38% for CKD stage G3 and 29% for stage G4/5. There was a trend toward higher achievement of LDL-C targets with increasing LLT intensity (adjusted odds ratios for moderate vs. low intensity 1.20; 95% confidence interval 0.92–1.56; high vs. low intensity 1.46; 1.02–2.09; Ptrend = 0.036). Conclusion: Many patients with CKD stage G3−G5 who are eligible for LLT are not treated, and those on LLT rarely achieve LDL-C targets. Keywords: cardiovascular disease, chronic kidney diseases, lipid-regulating agents, lipids, low-density lipoprotein cholesterol